Reduced Graphene‐Oxide‐Supported Titanium Oxynitride as Oxygen Reduction Reaction Catalyst in Acid Media. Issue 3 (8th August 2013) - Chisaka, Mitsuharu; Muramoto, Hirokazu
<x xml:space="preserve">Abstract</x> Inexpensive catalysts: A facile synthetic route to titanium oxynitride catalysts supported on reduced graphene‐oxide sheets is developed for use in polymer electrolyte fuel cell cathodes.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>